Implikasi Yuridis Riwayat tentang Kesalahan Penulisan dalam Mushaf Usmani - Rajafi, Ahmad (Al-Manahij: Jurnal Kajian Hukum Islam, 2017)
The history of writing error in the Qur'an derived from Aisha and justified by Khalifa Uthman bin Affan received a different responses among Islamic researchers, both from the strictly rejecting that history of writing (riwayat) until to those who accepted the existence the riwayat but with different "reading". On the legal side (juridical), the existence of that riwayat can result in juridical implications, especially in the methodological aspect. Such thought is not driven by the negative domain, but it must be in a positive domain, where the existence of that riwayat provides more progressive and responsive ijtihad, whether the answer is for the diversion to the difference of qiraâ€™at or not, the Islamic texts will be read more critically, so the legal purpose of â€œsuitable in every time and placeâ€ would be reached.